Two-Dimensional Materials, the Ultimate Solution for Future Electronics and Very-Large-Scale Integrated Circuits - Laixiang Qin; Li Wang (Nano-Micro Letters)
Highlights With the incessant down-scaling of electronics, traditional semiconductors like Si are encountered with insurmountable hurdles to maintain performance increase without bringing about additional issues of power consumption escalating, in this context, two-dimensional (2D) materials emerge as superior candidates to supersede or complement Si attributed to their marvelous electronic properties to further sustain the Moore’s law life. 2D materials-based electronics in More Moore and More than Moore’ regimes have attained promising achievements and showcased monumental potentials applications in low power consumption integrated circuits 2D materials-based integrated circuits have gone through a promising development, evolving from small-scale integrated circuits (ICs) to full-functioned processors. Whereas enormous endeavors are waited to be dedicated to realize large-scale ICs attributed to lack of large-scale 2D materials of electronic qualities and immature fabricating techniques.